Gap junction proteins in the blood-brain barrier control nutrient-dependent reactivation of Drosophila neural stem cells. - Spéder, P.; Brand, A.H. (Developmental Cell, 2014)
Neural stem cells in the adult brain exist primarily in a quiescent state but are reactivated in response to changing physiological conditions. How do stem cells sense and respond to metabolic changes? In the Drosophila CNS, quiescent neural stem cells are reactivated synchronously in response to a nutritional stimulus. Feeding triggers insulin production by blood-brain barrier glial cells, activating the insulin/insulin-like growth factor pathway in underlying neural stem cells and stimulating their growth and proliferation. Here we show that gap junctions in the blood-brain barrier glia mediate the influence of metabolic changes on stem cell behavior, enabling glia to respond to nutritional signals and reactivate quiescent stem cells. We propose that gap junctions in the blood-brain barrier are required to translate metabolic signals into synchronized calcium pulses and insulin secretion.